2018
DOI: 10.1007/s10554-018-1399-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of aspirin with identification of intimal morphology by optical coherence tomography in preventing event recurrence in patients with vasospasm-induced acute coronary syndrome

Abstract: Using optical coherence tomography (OCT), we found that there were morphological differences in the coronary intima between patients with vasospasm-induced acute coronary syndrome (VACS) and those with stable variant angina. We investigated whether aspirin use would protect against chest pain recurrence in patients with VACS. A retrospective cohort study was performed. Patients with ST-segment elevation who were confirmed to have VACS by a provocation test were included. OCT was performed at the index event an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The search engines were reviewed to identify 3645 related studies, among which 1303 articles were duplicates and 2414 articles did not fulfil the inclusion criteria and were excluded from the study. After removing these studies, four propensity-matched cohorts, 11 13 14 16 one retrospective analysis 12 and one prospective multicentre cohort 15 ( figure 1 ), including a total of 3661 patients (aspirin group, n=1695; no aspirin group, n=1966, table 1 ) were included in the study. Four studies underwent coronary provocation test, except for one study (Seong-Sik Cho, 2019) that used the electrocardiograph provocation test.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search engines were reviewed to identify 3645 related studies, among which 1303 articles were duplicates and 2414 articles did not fulfil the inclusion criteria and were excluded from the study. After removing these studies, four propensity-matched cohorts, 11 13 14 16 one retrospective analysis 12 and one prospective multicentre cohort 15 ( figure 1 ), including a total of 3661 patients (aspirin group, n=1695; no aspirin group, n=1966, table 1 ) were included in the study. Four studies underwent coronary provocation test, except for one study (Seong-Sik Cho, 2019) that used the electrocardiograph provocation test.…”
Section: Resultsmentioning
confidence: 99%
“… 13 In contrast, MI (HR=0.13; CI: 0.03 to 0.61; p=0.014) and chest pain recurrence (HR=0.29; CI: 0.12 to 0.71; p=0.006) were observed by Lee et al to have been significantly reduced by aspirin use among VSA patients during follow-up. 11 Lee et al showed that acute intimal tears and erosion identified by optical coherence tomography are susceptible to thrombosis leading to MI. Therefore, aspirin was evidenced to reduce adverse events in VSA patients with a greater number of thrombotic intracoronary lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective cohort study they followed for 48 months 154 patients who presented with VACS: using propensity score matching those patients were divided in equal groups of nonaspirin and aspirin use. Myocardial infarction (17% vs. 3%, p = 0.003) and chest pain recurrence (26% vs. 9%, p = 0.006) occurred more frequently in the non-aspirin group, showing that aspirin may have a protective effect on patients presenting with VACS [20].…”
Section: Evaluation Of Plaque and Tissue Characteristicsmentioning
confidence: 95%